Experimental study of piezoelectric and dielectric responses in Poly-L-lactic acid / Siti Hannah Mat Zin - Siti Hannah , Mat Zin (2022)
The piezoelectric d- and e-constants, as well as the elastic constant, c, and the dielectric constant, ε were determined as a function of frequency and temperature for oriented poly-L-lactic acid (PLLA) films with various elongation ratios and annealing temperatures using the dielectric resonance method. The findings are discussed in terms of a general theory of piezoelectricity for inhomogeneous systems, more specifically a disperse two-phase system. Five observations demonstrate that the piezoelectricity of PLLA film originates from the piezoelectric and optically active symmetry of PLLA crystallites and their orientation distribution. d14 component of the piezoelectric matrix is observed. The e14 is proportional to the product of orientation factor, Fc and crystallization fraction, Xc (Fc*Xc) of PLLA crystallites as determined by x-ray diffraction. The piezoelectric constants for a perfect crystal of PLLA was determined as e14 ~27 mC/m2 from the three-spring model and extrapolation to perfect orientation using the correlation of Fc*Xc assuming the PLLA crystallites are rigid. At ~100°C, the piezoelectric relaxation of PLLA is due to segmental mode relaxation in the amorphous phase within the crystalline region. A significant decrease in e14 with increasing temperature is caused by the non-crystalline phase softening, which results in a decrease in strain in the crystalline phase. The retardation of d14 is due to softening in the non-crystalline region caused by a parallel crystalline phase's stress concentration. An equivalent model is proposed that incorporates the PLLA film's higher order structure.